NON-MONETARY MOTIVATIONAL FACTORS AND JOB PERFORMANCE AMONG NON-EXECUTIVE EMPLOYEES AT A LOCAL ASSEMBLER IN SHAH ALAM, MALAYSIA - Nurbaizilah Baharuddin; Leviana Andrew; Muhammad bin Omar (Jurnal Penyelidikan Sains Sosial, 2020)
Motivational factors and job performance are two variables that had been frequently studied. However, many researchers concluded that monetary incentives have high impact on job performance and lesser researches had been done to the non-monetary factors such as flexible scheduling, physical working environment and training. Therefore, this study investigated the correlation between the non-monetary motivational factors and job performance among the non-executive employees at a local assembler in Shah Alam, Malaysia. There were 103 respondents participated in this study and it was confirmed that all non-monetary motivational factors were positively correlated with job performance. It was also found that among these factors, physical environment has the most influential impact on job performance at this firm. These findings implied that non-monetary motivational factors are equally important as monetary motivational factors and firms must prepare conducive working environment especially when it involves a factory with heavy machineries, hence, safety is crucial.